2000
DOI: 10.1128/jvi.74.5.2472-2476.2000
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Anti-Macrophage Inflammatory Protein 2 Antibody on Influenza Virus-Induced Pneumonia in Mice

Abstract: We investigated the effect of anti-macrophage inflammatory protein 2 immunoglobulin G (aMIP-2 IgG) on the progression of influenza virus-induced pneumonia in mice. When mice were infected with a mouse lung-adapted strain of influenza A/PR/8/34 virus by intranasal inoculation, neutrophil counts in the bronchoalveolar lavage fluid (BALF) increased in parallel with the kinetics of MIP-2 production, which peaked 2 days after infection. After intracutaneous injection of a dose of 10 or 100 g of aMIP-2 IgG once a da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
74
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 28 publications
5
74
1
Order By: Relevance
“…Furthermore, it has been reported that the level of the human CXC chemokine IL-8 is increased in patients with inflammatory airway disease, such as acute asthma, chronic obstructive pulmonary disease, and cystic fibrosis, characterized by high neutrophil numbers (37,38). Mouse homolog of human IL-8 (CXC chemokines), produced by bronchial epithelial cells, venous endothelial cells, alveolar macrophages, and neutrophils, have also been implicated as important mediators of lung immunity in airway inflammation models (36,39). To test the ability to produce neutrophil chemoattractant upon Ag stimulation in T cells, T cells were cultured with APCs and OVA peptide.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been reported that the level of the human CXC chemokine IL-8 is increased in patients with inflammatory airway disease, such as acute asthma, chronic obstructive pulmonary disease, and cystic fibrosis, characterized by high neutrophil numbers (37,38). Mouse homolog of human IL-8 (CXC chemokines), produced by bronchial epithelial cells, venous endothelial cells, alveolar macrophages, and neutrophils, have also been implicated as important mediators of lung immunity in airway inflammation models (36,39). To test the ability to produce neutrophil chemoattractant upon Ag stimulation in T cells, T cells were cultured with APCs and OVA peptide.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain single-cell suspensions, lung and nasal tissues were finely minced with scissors, incubated for 30 min at 37°C with 2 mg/ml collagenase A (Roche Diagnostics), and passed through a wire mesh. Samples were treated with Tris-NH 4 Cl (0.14 M NH 4 Cl in 17 mM Tris, adjusted to pH 7.2) to lyse erythrocytes and washed in RPMI 1640 medium supplemented with 10% FCS (RF 10 ). Cell numbers and cell viability were assessed via trypan blue exclusion using a hemocytometer.…”
Section: Recovery Of Leukocytes From Micementioning
confidence: 99%
“…Recent studies using the reconstructed virulent 1918 Spanish influenza pandemic virus (H1N1) or highly pathogenic H5N1 viruses to infect mice showed that neutrophils (and macrophages) predominate in the airways early after infection (2,3). Therapeutic blockade of the neutrophil-attracting chemokine MIP-2 was associated with reduced neutrophil recruitment and a milder lung pathology following infection with mouse-adapted A/PR/8/34 virus (PR8, H1N1), suggesting that dysregulated or excessive neutrophil responses might contribute to disease during severe influenza infection (4). In contrast, direct depletion studies using mAb RB6-8C5 (anti-Gr-1) enhanced the susceptibility of mice to infection with mouse-adapted influenza viruses (5,6), human virus strains of intermediate virulence (7), or with a recombinant virus bearing the surface glycoproteins of the 1918 pandemic virus (2).…”
mentioning
confidence: 99%
“…Of interest, neutrophil influx is much greater after IAV infection of SP-D or SP-A knockout mice than control mice (34,35). The role of neutrophils in clearance of IAV infection is unclear, with one study indicating that abrogation of the neutrophil response impaired recovery (10), whereas another found improved outcome (43). A recent study demonstrated that infection of mice with the IAV strain responsible for the 1918 pandemic caused marked neutrophil influx in the lung and that this effect was attributable to as yet undefined properties of the hemagglutinin (HA) molecule of that strain (31).…”
mentioning
confidence: 98%
“…The interactions of neutrophils in particular with IAV are of significance for several reasons. Early after IAV infection neutrophils infiltrate the airway probably due to release of chemokines that attract neutrophils (2,43). Of interest, neutrophil influx is much greater after IAV infection of SP-D or SP-A knockout mice than control mice (34,35).…”
mentioning
confidence: 99%